Optimization of Hybrid 1+ Proportional-Integral and Proportional-Integral-Derivative Controller for Load Frequency Regulation in Nonlinear Two-Area Power Systems Using Catch Fish Techniques - Pum, Vichheka; Audomsi, Sitthisak; Areeyat , Chatmongkol; Sawatphol, Palapol; Pakdeesuwan, Kunakorn; Luo, Jianhui; Chaiduangsri, Nuttapon (Engineering Access, 2026)
This investigation investigates the evolution of a hybrid frequency controller that is specifically engineered for nonlinear two-area power systems. The controller ensures reliable frequency regulation by incorporating the most efficient components of both 1+PI and PID control methodologies, particularly when faced with complex issues such as GRC and GDB. In order to achieve the optimal calibration of the control parameters, the CFOA is implemented. This algorithm effectively traverses the search space and avoids suboptimal local optima by utilizing established fishing techniques. The performance criterion for the proposed method is ITAE, and simulations are conducted on a two-area power system model with 0.2 per unit load variations. The results suggest that the hybrid controller significantly reduces overshoot, undershoot, and settling time, while simultaneously guaranteeing a continuous tie-line power flow. The controller’s efficacy is extraordinary, with an ITAE of approximately 0.0336. These results emphasize its suitability for complex multi-area power networks and suggest potential applications in future systems, such as renewable energy or fluctuating demands.